E-Commerce and Trust Services- Application in Albania - Açka, Shqiponjë; Açka, Elvira (Richtmann Publishing, 2012)
The aim of this paper is to define the impact that should have application of e-commerce from Albanian businesses in labormarket of Albanian accounting experts. The primary objectives of this study are to show the new areas that will be created for accountingexperts from application of this new service in our market and also what are the necessary qualifications for professional’s experts foroffering trust services with high quality. For success these objectives initially in this paper I will analyze what are trust services and theprocedures that are follow in foreign countries that apply from many years with success trust services; also I will give one panorama ofnecessary knowledge for one expert for realize with quality these services and to offer assurance for all groups interested in utilization ofe-commerce. All this material will help me to define results of this study if Albanian accounting experts in one near future will be ready ornot for offer with success trust services. For these results I will take in consideration also training programs that professionalorganizations in accounting field in Albania offer for accounting experts to definite also what are additional knowledge for trust servicesand how available will be this knowledge for our experts.